Development of broccoli by-products as carriers for delivering EGCG. (15th December 2019) - Shi, Meng; Ying, Dan-Yang; Hlaing, Mya Myintzu; Ye, Jian-Hui; Sanguansri, Luz; Augustin, Mary Ann
Highlights: Different fractions of broccoli by-products had different affinities for EGCG. Puree and pomace powders had higher adsorption capacity for EGCG than juice. EGCG adsorption onto pomace and puree suited Langmuir and Freundlich models. FTIR indicates stronger interaction of puree with EGCG than pomace. Puree had the highest protection on EGCG during in vitro digestion. Abstract: Novel delivery systems for epigallocatechin gallate (EGCG) were developed using broccoli by-products and their fractions as carriers. Puree and pomace from broccoli by-products had higher adsorption capacities for EGCG than juice at 25 °C (43.20 mg g −1, 39.47 mg g −1 and 25.22 mg g −1 dry weight for pomace, puree and juice respectively). Chemical sorption is the rate-controlling step for EGCG-broccoli interactions. Langmuir and Freundlich models well described the adsorption of EGCG onto puree and pomace. FTIR results indicated that EGCG-puree had stronger interaction than EGCG-pomace. When the same level of EGCG (∼26 mg) was added to different matrices, more EGCG (∼20%) was recovered from the in vitro digestion system of EGCG-loaded puree than from the EGCG-loaded pomace (14%) and neat EGCG (9%). The antioxidant capacity of the whole digesta was positively correlated with the EGCG levels. Broccoli by-products are promising carriers for delivering and stabilizing EGCG through gastrointestinal digestion.